PENGARUH METODE 5S (SEIRI, SEITON, SEISO, SEIKETSU, DAN SHITSUKE) TERHADAP KINERJA KARYAWAN - Nuril Huda, Achmad Rifqi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this study is to determine the effect of the 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) on employee performance in Amstirdam Coffee & Roastery Malang. The research type is an explanatory research, which explains about the causal relation between variables from the research hypothesis. This study involved 42 respondents. The selected respondents for this study were all employees of Amstirdam Coffee & Roastery Malang. This research utilized a Likert Scale for its instrument. The utilized data analysis technique for this research was multiple linear regression analysis. The conducted statistical testing for this research were instrument testing, classical assumptions testing, and hypothesis testing (t-test and F-test). The results of this research showed that Seiri, Seiton, and Shitsuke have a partial, significant effect towards employee performance. The results of this research also showed that the 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) have a simultaneous, significant effect towards employee performance.